Incidence, puberty, and fertility in 45, X/47, XXX mosaicism: Report of a patient and a literature review. Issue 7 (9th May 2017) - Lim, Han Hyuk; Kil, Hong Ryang; Koo, Sun Hoe
Abstract : Turner syndrome (TS), characterized by short stature and premature ovarian failure, is caused by chromosomal aberrations with total or partial loss of one of the two X chromosomes. Spontaneous puberty, menarche, and pregnancy occur in some patients depending on the abnormality of the X. Moreover, spontaneous pregnancy is uncommon (<0.5%) for TS with 45, X monosomy. Among TS patients, 45, X/47, XXX karyotype is extremely rare. Previous reports have demonstrated that TS with 45, X/47, XXX is less severe than common TS due to higher occurrence of puberty (83%), menarche (57–67%), and fertility (14%) and lower occurrence of congenital anomalies (<5%). However, TS mosaicism may not reduce the frequency of short stature. We diagnosed a 10‐year‐girl with TS with 45, X/47, XXX mosaicism who presented with short stature. She showed mild TS phenotype including short stature but had spontaneous puberty. Based on our case and previous reports, we expect that girls with 45, X/47, XXX mosaicism may progress through puberty normally, without estrogen therapy. Therefore, it is necessary to consider specific guidelines for clinical decisions surrounding pubertal development and fertility in TS with 45, X/47, XXX karyotype.